2022
DOI: 10.3390/ijerph19084886
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Distribution, Composition, and Inventory of Plastic Debris on the Yugang Park Beach in Zhanjiang Bay, South China Sea

Abstract: Plastic debris contamination in marine environments is a global problem that poses a considerable threat to the sustainability and health of coastal ecosystems. Marine beaches, as the key zones where terrestrial plastic debris reach coastal waters, are faced with the increasing pressures of human activities. In this study, we explored the distribution, composition, and inventory of plastic debris over seasonal and tidal zones at the Yugang Park Beach (YPB) in Zhanjiang Bay, South China Sea, to provide a baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 81 publications
0
14
0
1
Order By: Relevance
“…According to relevant statistics [48], there are about 27 rubber and plastic products enterprises in the Zhanjiang area, with an annual production of 85,000 tons of plastic products, 411,700 tons of primary plastic products, and 2643 tons of agricultural plastic film. Zhang et al [52] demonstrated that microplastics found on the beaches of ZJB Yugang Park can originate from plastic products such as polyethylene, polystyrene, polyvinyl chloride resin, and polypropylene. Therefore, the sources of PAEs in ZJB are likely derived from plastic products as well as the manufacturing processes of plastic products enterprises.…”
Section: Source Of Plastic Pollutionmentioning
confidence: 99%
“…According to relevant statistics [48], there are about 27 rubber and plastic products enterprises in the Zhanjiang area, with an annual production of 85,000 tons of plastic products, 411,700 tons of primary plastic products, and 2643 tons of agricultural plastic film. Zhang et al [52] demonstrated that microplastics found on the beaches of ZJB Yugang Park can originate from plastic products such as polyethylene, polystyrene, polyvinyl chloride resin, and polypropylene. Therefore, the sources of PAEs in ZJB are likely derived from plastic products as well as the manufacturing processes of plastic products enterprises.…”
Section: Source Of Plastic Pollutionmentioning
confidence: 99%
“…Selain dari aktivitas pengunjung, sampah yang tertinggal di ke tiga zona ini juga disebabkan adanya proses pasang surut air laut. Pada saat pasang tertinggi terjadi, sampah plastik yang yang memiliki massa yang ringan dapat terbawa dari perairan kemudian tertinggal saat surut terendah (Zhang et al, 2022).…”
Section: Pembahasanunclassified
“…In the Mediterranean sea, UNEP indicated that marine litter is mainly linked to summer tourism (UNEP 2009). In this sense, studies have evaluated the seasonal evolution of plastic waste on the beach during summer tourism and found that plastic items volume is higher during the summer compared to other seasons (Pervez et al 2020 ; Gómez et al 2020 ; Zhang et al 2022 ). Indeed, Ariza et al ( 2008 ) reported that 13% of collected litter and waste from the Lloret Centre beach during summer tourism on the Catalan coast was discarded and left on the sand by visitors.…”
Section: Plastic Pollution In Morocco: Sources and Fatementioning
confidence: 99%